Impact of RKVY Programme on Income Distribution Pattern of Piggery Beneficiaries - A. Lavanya; G. Ganga Raju; J. Suresh; K. Sakunthala Devi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Rastriya Krishi Vikas Yojana (RKVY) draws up plan to integrate agriculture with allied enterprises. This study aims at assessing the impact of RKVY programme on income distribution of piggery beneficiaries in Chittoor, Kadapa, Kurnool and Nellore districts of Andhra Pradesh. Thirty beneficiaries were purposively selected since they have completed 3 years of pig rearing and were personally interviewed for collection of data. The net income was found to be Rs.58,590, Rs.2,05,577 and Rs.2,70,269 in the 1st, 2nd and 3rd years, respectively. Savings increased as the years passed by. The Gini concentration ratios in respect of the income were found to be 0.6989, 0.5353, and 0.4454 in respective years.